PENGARUH KONDISI EKONOMI ORANG TUA TERHADAP HASIL BELAJAR IPAS SISWA KELAS VA SD NEGERI SIKUMANA 2 - Agata Desa, Kornelia; E. Noya Nahak, Kristina; Marselina Nitte, Yulsy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the influence of parents' economic conditions on the IPAS learning outcomes of Grade VA students at SD Negeri Sikumana 2. The study employed a quantitative approach using an ex post facto design. The population consisted of 20 Grade VA students, all of whom were selected as the research sample using the total sampling technique. Data were collected through a Likert-scale questionnaire to measure parents' economic conditions and documentation of students' IPAS learning outcomes. Data analysis was conducted using simple linear regression with the assistance of SPSS version 25. The findings revealed that parents' economic conditions had a positive and significant effect on students' IPAS learning outcomes, with a significance value of 0.030 (<0.05). The regression coefficient of 0.055 indicates that every improvement in parents' economic conditions is followed by an increase in students' learning outcomes. Furthermore, the coefficient of determination (R²) of 0.462 shows that parents' economic conditions contributed 46.2% to the students' IPAS learning outcomes, while the remaining 53.8% was influenced by other factors outside this study. Therefore, it can be concluded that parents' economic conditions significantly affect the IPAS learning outcomes of Grade VA students at SD Negeri Sikumana 2.